MENINGKATKAN KEAKTIFAN BELAJAR IPAS SISWA KELAS IV MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) - Miftakhul Nurjannah, Aldila; Nani Mediatati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Low student engagement can hinder their ability to develop their skills, thereby not aligning with the expected learning objectives. This study aims to increase the engagement of fourth-grade students at SDN Kalicacing 02 Salatiga by using the Problem-Based Learning (PBL) model. This type of research is Classroom Action Research (CAR). The participants in this study were 17 students from the fourth grade of SDN Kalicacing 02 Salatiga. The research design is based on the CAR design by Kemmis and McTaggart (1988) and was conducted in two cycles. Data were collected through observation, questionnaires, and documentation. The data analysis techniques used were descriptive qualitative and quantitative techniques. The success criteria for this research were that at least 75% of the fourth-grade students at SDN Kalicacing 02 Salatiga should have a high and/or very high level of engagement. The results of the study showed that the engagement of fourth-grade students at SDN Kalicacing 02 Salatiga can be improved by using the Problem-Based Learning model. Observation results from the first cycle showed an engagement score percentage of 65.56%, which then increased to 82.60% in the second cycle. Meanwhile, the student engagement questionnaire results showed a percentage score of 63.97% in the first cycle, which increased to 80.78% in the second cycle. The actions in the second cycle met the research success criteria of 75% of the students. Therefore, it can be concluded that the Problem-Based Learning model can increase the engagement of fourth-grade students at SDN Kalicacing 02 Salatiga.